2023
DOI: 10.1109/tii.2022.3205366
|View full text |Cite
|
Sign up to set email alerts
|

A Multilayer Deep Learning Approach for Malware Classification in 5G-Enabled IIoT

Abstract: 5G is becoming the foundation for the Industrial Internet of Things (IIoT) enabling more effective lowlatency integration of artificial intelligence and cloud computing in a framework of a smart and intelligent IIoT ecosystems enhancing the entire industrial procedure. However, it also increases the functional complexities of the underlying control system, and introduce new powerful attacks vectors leading to severe security and data privacy risks. Malware attacks are starting targeting weak but highly connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…As demonstrated in the above discussion, utilizing SPP 50 enables us to input varying sizes of training samples into CNN without compromising information. This approach allows using traditional platform‐based malware samples to train models for IoT malware variant detection 51 . By leveraging a larger sample set, we can significantly enhance detection accuracy and improve our ability to identify and mitigate emerging threats.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated in the above discussion, utilizing SPP 50 enables us to input varying sizes of training samples into CNN without compromising information. This approach allows using traditional platform‐based malware samples to train models for IoT malware variant detection 51 . By leveraging a larger sample set, we can significantly enhance detection accuracy and improve our ability to identify and mitigate emerging threats.…”
Section: Methodsmentioning
confidence: 99%
“…This approach allows using traditional platform-based malware samples to train models for IoT malware variant detection. 51 By leveraging a larger sample set, we can significantly enhance detection accuracy and improve our ability to identify and mitigate emerging threats.…”
Section: ) Convolutional Neural Network Modulementioning
confidence: 99%
“…Our proposed method outperforms the existing deep malware detection and image classification methods by a notable margin. In addition to that, we illustrate an optimization strategy for deploying our deep model in low-power edge devices to reveal the practicability of deep, efficient malware detection for securing future solutions, including securing IoT and 5G/6G infrastructures [35,36]. To the best concern, this is the first work in the literature demonstrating the optimization and practicability of malware detection on real-edge hardware with sophisticated experiments.…”
Section: Introductionmentioning
confidence: 99%
“…This is achieved by utilizing a client and a server [12]. Servers in the cloud can detect malicious software in files sent to them by clients in the cloud [13]. Recent studies have demonstrated that malware detection rates can be improved and that each malware sample can be thoroughly analyzed using cloudbased detection [14].…”
Section: Introductionmentioning
confidence: 99%